Transmissible Gastroenteritis MECHANISMS RESPONSIBLE FOR DIARRHEA IN AN ACUTE VIRAL ENTERITIS IN PIGLETS - Butler, D. G. (1974)
We studied 3-wk-old piglets 40 h after experimental infection with transmissible gastroenteritis (TGE) virus to identify the mechanisms of diarrhea in this disease and to better understand infectious diarrhea in humans. Using continuous segmental marker perfusion in four regions along the gut, we found significant increases in net intraluminal accumulation of water and electrolytes only in the proximal jejunum, the region infected by the virus. In this jejunal segment studied in vivo, unidirectional sodium flux, extracellular fluid (ECF) to lumen, significantly increased, lumen to ECF significantly decreased, compared with matchfed littermates. The standard perfusate rendered hypertonic by adding mannitol (450 mosmol/kg), in the same segment of normal pigs, caused only an increase in ECF to lumen flux of sodium. TGE did not alter gross villous structure or intraluminal bacteria, bile salts, lactate, pH, or osmolality. Epithelial cell migration was accelerated in the jejunum of infected pigs. Isolated in suspension, these cells from TGE pigs exhibited increased active and passive sodium efflux, cells from mannitol-perfused pigs exhibited only increased active sodium efflux. In this viral enteritis, altered sodium transport occurring in the jejunum, the region of the intestine infected appears to be associated with defective epithelial cell function. The precise nature of the abnormalities in sodium transport, their relationship to disturbances of transport of other solutes, and to virus epithelial cell interaction remain to be defined.